Circular economy approach for wastewater treatment farming in Bangpakong River basin - N. Surinkul (2021)
© 2020 Published under licence by IOP Publishing Ltd. Bangpakong River is one of river basins that faced the pollution problem in Thailand. This river is located in the downstream of central pain of Thailand and flows into the sea at the gulf of Thailand. Water quality problems in the last decade of this river basin are appeared from the low water quality index with evidences such as dead of fish, black color of water, low Dissolved Oxygen (DO) concentrations, high organics and nutrients concentrations, high contaminated of coliform bacteria. All wastewater is controlled by the environmental law. Only wastewater from agriculture part is not yet properly managed. The objective of this study was to quantify the mass and material flows in agricultural farms such as pig, fish and prawn farms. Circular economy concept as reuse of wastewater in agricultural farms was approached in scenario. Surveys, questionnaires and water samplings were taken for farms. Information and mass flows within the farms were analyzed. This study found that the main source of pollution from these farms mostly resulted from the effluent of wastewater in term of Biological Oxygen Demand (BOD) and Total Nitrogen (TN) loads, were discharged into the environment. The hot spot areas were canals which flow to the river. Mass flows in pig farm revealed that BOD and TN loads to the environment were 90, and 120 tons/year. In which, calculated thresholds were 30 and 60 tons/year for BOD and TN. Similar results also found from aquaculture farms which contributes BOD and TN loads of 187 and 77 tons/year for fish farms and 156 and 84 tons for prawn farms. In this study, calculated reuse as circular economy approach about 50% of farm wastewater to agricultural field could provide the key role of BOD and TN reduction to the environment, and meeting the threshold level.